Potential Bioactive Compounds of Melastoma malabathricium Leaf Extract in Feed on Growth Performance and Survival Rate of Tilapia Fry in Brackish Water - Muhammad Kasnir; Khairun Nisaa; Agria Budi Darmawan; Nuril Farizah; Iman Sudrajat (Department of Aquaculture, 2023)
Tilapia fish have a salinity tolerance of 0 to 10 ppt. However, the increase in salinity causes a decrease in the growth rate of these fish. In addition, the rapid maturation of the gonads causes this fish to experience a slowdown in growth. This study aimed to know the effect of giving Melastoma malabathricum extract on the growth performance of tilapia fry reared in brackish water. The study consisted of treatment with 0, 1, 3, and 6 g/kg of feed with three replications of M. malabathricum leaf extract. M. malabathricum leaf extract was mixed in feed with a CMC concentration of 2%. Feed is given as much as 3% body weight twice a day. Observations of growth performance were carried out every seven days, and the amount of feed was readjusted based on the results of sampling fish weight. The study was conducted for 70 days using brackish water with a salinity of 8 ppt. Based on the study results, it was found that the highest growth of tilapia fry at the end of the study was found in the treatment of 1 g/kg feed. The same thing was also found in measuring feed efficiency, survival, and specific growth rate. It indicated that the best concentration of M. malabathricum leaf extract in supporting the growth performance of tilapia fry was 1 g/kg feed.